Public preferences for pasture landscapes and the role of scale heterogeneity - Henning Schaak; Oliver Mußhoff (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2018)
Despite its relevance for agricultural production, biodiversity and landscape aesthetics, grazing livestock is rarely considered in research on public landscape preferences. This paper studies public preferences for pasture usage in Germany by the means of a discrete choice experiment. The results indicate that there is a general willingness to pay (WTP) for livestock presence in landscape. The mean WTP is independent of its density. The paper discusses the implications of different econometric models and the role of preference heterogeneity on the results. The results show that a detailed analysis of the preference heterogeneity can provide deeper insights on their structure.
Keywords: C25; Q15; 330; Discrete-Choice-Experiment; Public Landscape Preferences; Livestock; Mixed Logit Model